Money, debt and politics - Cardoso, José Luís, author.
1 online resource (viii, 112 pages)
Keywords: "This book presents an innovative history of the first Portuguese public bank, by exploring the relationship between banking activities and the political context. It provides an overview of the origins of the banking system in Portugal, and also in Brazil, and explores new archive materials related to the first years of activity of the Bank of Lisbon and to the public debates on monetary and public finance topics. It discusses the main features of the Bank of Lisbon: a private bank with a mandate to issue banknotes for the purposes of regulating monetary circulation, and with the function of financing the State for current payments, as well as for the amortisation of public debt and the creation of new debt. The aim of contributing to the re-establishment of public trust and credit conferred upon the Bank of Lisbon the status of a quasi-central bank with the obligations of lending and issuing money. This historical case study offers new insights for a better understanding of the role of banks on the regulation of monetary circulation and on the management of sovereign debt. By stressing the relevance of the political context, it also illustrates the key issues of trust, independence and rules associated to decision-making processes in the study of European banking history. The main focus is the link between banking practices and the political environment. However, the reader will also engage in discussions on theoretical and economic policy issues on the main economic topics under survey: money, paper-money, public debt, credit system"--